Antibacterial properties of seaweed and oyster extracts and their effects on pathogenic bacteria tolerance, immune status, growth and proximate composition in feeding trials of the red tilapia, Oreochromis sp. juveniles - Mastoi, Ali Muhammad
Consistent expansion of aquaculture practices has led in generating increased interest to understand various fish diseases and their control measures. The occurrence of diseases in aquaculture fish farm is primarily due to several factors related to rearing methods and deteriorating environmental conditions. Infectious diseases are also a major problem in cage grown fishes causing heavy loss to the fish farmers. The most effective methods of controlling diseases in aquaculture practices are through strengthening the defense mechanisms of the fish by prophylactic administration of effective immune-stimulants.